2018
DOI: 10.18632/oncotarget.24142
|View full text |Cite
|
Sign up to set email alerts
|

The effects of taxanes, vorinostat and doxorubicin on growth and proliferation of Echinococcus multilocularis metacestodes assessed with magnetic resonance imaging and simultaneous positron emission tomography

Abstract: Cytostatic drugs used in cancer therapy were evaluated for their capacity to inhibit Echinococcus multilocularis metacestode growth and proliferation. Metacestode tissues were exposed in vitro to docetaxel, doxorubicin, navelbine, paclitaxel, and vorinostat for 1 week, then incubated in drug-free culture, and thereafter metacestodes were injected into the peritoneum of Meriones unguiculatus. Magnetic resonance imaging (MRI) and simultaneous positron emission tomography (PET) were applied to monitor in vivo gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Nevertheless, such drugs are a promising starting point for screening approaches with limited resources, and potentially allow to gain more insights about their possible modes of action and thus potentially valuable targets where research should be focused. Most studies on drug repurposing against AE evaluated an overall relatively small number of compounds, including anti-cancer compounds ( Naguleswaran et al, 2006 ; Gelmedin et al, 2008 , 2010 ; Spicher et al, 2008a ; Hübner et al, 2010 ; Hemer and Brehm, 2012 ; Schubert et al, 2014 ; Huang et al, 2018 ; Joekel et al, 2018 ; Förster et al, 2019 ), anti-infective drugs ( Reuter et al, 2003 , 2006 ; Stettler et al, 2003 ; Spicher et al, 2008b ; Stadelmann et al, 2010 , 2011 ; Küster et al, 2011 , 2014a , 2014b , 2015 ; Rufener et al, 2018a , 2018b ), immunotherapeutics ( Emery et al, 1998 ; Pfister et al, 1989 ; Godot et al, 2003 ; Boubaker et al, 2015 ; Wang et al, 2018 ; Jebbawi et al ), and natural products ( Albani Clara and Elissondo María, 2014 ; Albani et al, 2015 ; Yuan et al, 2016 ; Hizem et al, 2019 ). In the following sections, we will focus more on anti-infective drugs, and in particular on the group of anti-malarials.…”
Section: Identification Of Novel Drugs Against Alveolar Echinococcosimentioning
confidence: 99%
“…Nevertheless, such drugs are a promising starting point for screening approaches with limited resources, and potentially allow to gain more insights about their possible modes of action and thus potentially valuable targets where research should be focused. Most studies on drug repurposing against AE evaluated an overall relatively small number of compounds, including anti-cancer compounds ( Naguleswaran et al, 2006 ; Gelmedin et al, 2008 , 2010 ; Spicher et al, 2008a ; Hübner et al, 2010 ; Hemer and Brehm, 2012 ; Schubert et al, 2014 ; Huang et al, 2018 ; Joekel et al, 2018 ; Förster et al, 2019 ), anti-infective drugs ( Reuter et al, 2003 , 2006 ; Stettler et al, 2003 ; Spicher et al, 2008b ; Stadelmann et al, 2010 , 2011 ; Küster et al, 2011 , 2014a , 2014b , 2015 ; Rufener et al, 2018a , 2018b ), immunotherapeutics ( Emery et al, 1998 ; Pfister et al, 1989 ; Godot et al, 2003 ; Boubaker et al, 2015 ; Wang et al, 2018 ; Jebbawi et al ), and natural products ( Albani Clara and Elissondo María, 2014 ; Albani et al, 2015 ; Yuan et al, 2016 ; Hizem et al, 2019 ). In the following sections, we will focus more on anti-infective drugs, and in particular on the group of anti-malarials.…”
Section: Identification Of Novel Drugs Against Alveolar Echinococcosimentioning
confidence: 99%
“…After, magnetic resonance imaging and simultaneous positron emission tomography were applied to monitor in vivo growth of drug-exposed Echinococcus multilocularis. The in vivo growth of metacestodes was suppressed until 3 months postinfection, thereafter, parasite tissues enlarged up to 3 cm 3 [51].…”
Section: Paclitaxelmentioning
confidence: 98%
“…Finally, in an in vitro cyst incubation it was shown that paclitaxel resulted in dramatic alterations within 3 to 5 days after initiation of treatment [50]. In another experiment, Huang et al (2018) evaluated the effect of paclitaxel on growth and proliferation of Echinococcus multilocularis metacestodes. They exposed metacestode tissues in vitro to paclitaxel (2, 5, and 10 μM) for one week and, thereafter, were injected into the peritoneum of Meriones unguiculatus.…”
Section: Paclitaxelmentioning
confidence: 99%
See 2 more Smart Citations